Alkali metal battery electrolyte additive, electrolyte, and preparation and application thereof
By adding ionic liquids with tetraacetonitrile copper (I) cations and fluorine-containing Lewis alkali anions to the alkali metal battery electrolyte, the formation of electrostatic shielding and stable SEI film is achieved, the problem of alkali metal dendrites is solved, and the cycle life and safety of the battery are improved.
Patent Information
- Application Number
- CN202210522992.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-13
AI Technical Summary
The growth of alkali metal dendrites in alkali metal batteries leads to unstable battery performance and safety risks. The existing film-forming additives are fragile and cannot inhibit dendrites' growth for a long time.
An ionic liquid composed of tetraacetonitrile copper (I) cation (TAC cation) and fluorine-containing Lewis alkali anion is used as an electrolyte additive to inhibit the growth of alkali metal dendrites by electrostatic shielding and forming a stable SEI film.
It effectively improves the cycle life and electrochemical performance of alkali metal batteries, enhances the safety of the battery, and reduces the risk of rupture of SEI film.
Smart Images

Figure CN114865108B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alkali metal battery electrolyte additive, an electrolyte and preparation and application thereof, belonging to the technical field of alkali metal batteries. Background Art
[0002] Alkali metal batteries generally refer to batteries whose negative electrodes are lithium, sodium, potassium and their alloys. Alkali metals have extremely high theoretical specific capacity, low redox potential and low density, so alkali metal batteries with them as negative electrodes are considered to be one of the most promising high-energy storage devices with broad application prospects.
[0003] However, alkali metal batteries are difficult to apply on a large scale due to their poor safety and unstable cycle performance. An important factor affecting the performance of alkali metal batteries is their poor interfacial stability. During the first cycle of charge and discharge of alkali metal batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material. This passivation layer is called the solid electrolyte interface film (SEI film for short), and its main components are small molecule organic matter, organic polymers and inorganic compounds containing alkali metals. The SEI film can isolate the alkali metal electrode in the inner layer of the film from the electrolyte, thereby preventing the continuous corrosion of the electrolyte and playing a role in protecting the alkali metal electrode. However, the SEI film will also reduce the ion transmission energy barrier between the electrode and the electrolyte, consume the electrolyte, and affect the performance of the battery. Therefore, a suitable SEI film should have the following properties: (i) thin thickness and low electrolyte consumption; (ii) good stability, no continuous decomposition, good mechanical properties, chemical stability and electrochemical stability; (iii) high alkali metal ion conductivity; (iv) dense structure.
[0004] However, the SEI film spontaneously formed by the alkali metal electrode and the electrolyte has unsatisfactory properties such as strength and toughness. During the deposition / stripping process of alkali metals, the uneven deposition of alkali metals leads to the growth of alkali metal dendrites, and the growth of alkali metal dendrites easily leads to the rupture of the SEI film, thereby losing its protective effect. The main problems of dendrite growth are also manifested in the following aspects: first, dendrite growth leads to a reduction in active alkali metals and a decrease in battery energy density; second, dendrites piercing the diaphragm will cause the battery to short-circuit, causing fire and explosion, and reducing battery safety.
[0005] At present, most of the research on inhibiting the growth of alkali metal dendrites focuses on adding film-forming additives to the electrolyte to improve the composition of the SEI film and enhance the mechanical strength and other properties of the SEI film, thereby preventing the dendrites from growing further and piercing the diaphragm. However, the effective substances introduced to improve the film-forming performance or the nanostructured interface layer constructed by the currently used film-forming additives are fragile. Once the effective substances introduced in the additives are consumed or the nanostructured interface layer is broken, the function of inhibiting the growth of alkali metal dendrites is lost, which leads to more intense growth of alkali metal dendrites, resulting in a decrease in electrochemical performance and serious safety hazards. Summary of the invention
[0006] In view of this, in order to solve the problem of alkali metal dendrite growth in alkali metal batteries in the prior art, the purpose of the present invention is to provide an alkali metal battery electrolyte additive, electrolyte and its preparation and application. The electrolyte additive is applied to the electrolyte of the alkali metal battery, which can not only inhibit the growth of alkali metal dendrites and improve the cycle life of the alkali metal battery through the comprehensive effects of "electrostatic shielding" and "forming a stable SEI film", but also improve the electrochemical performance of the battery. The SEI film and alkali metal electrode can both inhibit the growth of alkali metal dendrites, improve the safety of the battery, and make the battery have good electrochemical performance.
[0007] To achieve the purpose of the present invention, the following technical solutions are provided.
[0008] An alkali metal battery electrolyte additive, the additive is an ionic liquid composed of tetraacetonitrile copper (I) cations (TAC cations) and fluorine-containing Lewis base anions; the fluorine-containing Lewis base anions are one or more of tetrafluoroborate ions (BF4ˉ), hexafluorophosphate ions (PF6ˉ), trifluoromethanesulfonate ions (CF3SO3ˉ), bistrifluoromethylsulfonyl imide ions (TFSIˉ) and bisfluorosulfonyl imide ions (FSIˉ).
[0009] Preferably, the electrolyte additive is one or more of tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4), tetraacetonitrile copper (I) hexafluorophosphate ([(CH3CN)4Cu]PF6) and tetraacetonitrile copper (I) trifluoromethanesulfonate ([(CH3CN)4Cu]CF3SO3).
[0010] An alkali metal battery electrolyte, the electrolyte comprising an organic solvent, an alkali metal salt and the electrolyte additive of the present invention; in the electrolyte, the concentration of the electrolyte additive is 0.5 mg mL -1 ~2mg mL -1 .
[0011] The organic solvent and alkali metal salt are organic solvents and alkali metal salts used in alkali metal batteries in the prior art.
[0012] Preferably, the organic solvent is one or more of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,3-dioxolane (DOL), 4-methyl-1,3-dioxolane (4-MeDOL), dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), 1,2-dimethoxypropane (DMP), diethylene glycol dimethyl ether (DG), N-methylpyrrolidone (NMP), propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methylpropyl carbonate (MPC), dimethylformamide (DMF), γ-butyrolactone (BL), methyl acetate (MA) and ethyl acetate (EA).
[0013] Preferably, the alkali metal salt is one or more of alkali metal hexafluorophosphate, alkali metal tetrafluoroborate, alkali metal bistrifluoromethylsulfonyl imide salt and alkali metal perchlorate.
[0014] More preferably, the organic solvent is composed of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1, or 4-methyl-1,3-dioxolane (4-MeDOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1, or ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, or ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, Or it is composed of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, or it is composed of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1; the alkali metal salt is one of alkali metal hexafluorophosphate, alkali metal tetrafluoroborate, alkali metal bistrifluoromethylsulfonyl imide and alkali metal perchlorate; in the electrolyte, the concentration of the alkali metal salt is 1 mol / L.
[0015] Preferably, in the electrolyte, the concentration of the electrolyte additive is 1 mg mL -1 .
[0016] A method for preparing the electrolyte of the present invention, the method steps are as follows:
[0017] (1) in an inert gas atmosphere in which oxygen and water contents are both less than 1 ppm, adding an alkali metal salt to an organic solvent and mixing them uniformly to obtain a mixed solvent;
[0018] (2) Continuing in the above-mentioned inert gas atmosphere, adding the electrolyte additive of the present invention to the mixed solvent, mixing evenly, and standing for 15 minutes to 60 minutes to obtain the electrolyte of the present invention;
[0019] The inert gas is helium, neon, argon, krypton, xenon or radon.
[0020] Preferably, in step (2), the electrolyte additive and the mixed solvent are mixed uniformly by means of magnetic stirring and ultrasonic dispersion.
[0021] More preferably, in step (2), magnetic stirring is first performed for 1 hour, and then ultrasonic dispersion is performed for 1 hour to ensure that the electrolyte additive and the mixed solvent are evenly mixed.
[0022] An application of the electrolyte of the present invention, the application being: before electrochemical cycling, in an inert gas atmosphere with oxygen and water contents both less than 1 ppm, immersing an alkali metal electrode body in the electrolyte of the present invention, allowing the alkali metal to pre-react with the electrolyte, the reaction temperature being 20° C. to 65° C., the reaction time being 0.5 h to 2 h, and after the reaction is completed, an SEI film is in situ formed on the surface of the alkali metal electrode body, that is, obtaining an alkali metal electrode with an SEI film;
[0023] The inert gas is helium, neon, argon, krypton, xenon or radon.
[0024] Preferably, the reaction time is 0.5 h to 1 h.
[0025] An alkali metal battery, wherein the electrolyte of the battery is the electrolyte of the present invention;
[0026] Alternatively, the negative electrode in the battery is an alkali metal electrode with a SEI film as described in the present invention;
[0027] Alternatively, the electrolyte of the battery is the electrolyte described in the present invention and the negative electrode in the battery is an alkali metal electrode with a SEI film described in the present invention.
[0028] Beneficial Effects
[0029] (1) The present invention provides an alkali metal battery electrolyte additive, wherein the anion of the additive is compatible with the alkali metal battery electrolyte system and is beneficial for providing additional fluorine elements for the SEI film formation process; the cation of the additive is TAC cation, which can provide cuprous ions (Cu + ), due to Cu +Adjustment of the electrolyte solvation structure promotes the fluorine element in the electrolyte to generate alkali metal fluoride, so that the alkali metal fluoride is used as a component of the SEI film. The increase in the content of alkali metal fluoride in the SEI film increases the mechanical strength of the SEI film, which can effectively inhibit the growth of alkali metal dendrites, and is also beneficial to improve the conduction rate of alkali metal ions, thereby improving the cycle performance and life of the battery. At the same time, the TAC cation will cover the dendrite tip where the negative charge is gathered through electrostatic adsorption, forming an effective shielding effect, preventing the continuous growth of the dendrite, and reducing the risk of the generated SEI film rupture with the long-term circulation of the alkali metal battery. In summary, the electrolyte additive of the present invention is applied to the electrolyte of the alkali metal battery, which can improve the cycle life and working performance of the alkali metal battery through the combined effects of "electrostatic shielding" and "forming a stable SEI film".
[0030] (2) The present invention provides an electrolyte. Since the electrolyte contains the electrolyte additive described in the present invention, the electrolyte is applied to an alkali metal battery to inhibit the growth of alkali metal dendrites and improve the cycle life and working performance of the alkali metal battery.
[0031] (3) The present invention provides a method for preparing an electrolyte, which is simple; the method further uses magnetic stirring and ultrasonic dispersion to uniformly mix the electrolyte additive and the mixed solvent, thereby ensuring the uniformity of the added ionic liquid and the mixed solvent, and avoiding concentration polarization caused by the concentration gradient in the system. In the application of batteries or electrodes, the formed SEI film can be made uniform and dense, thereby enabling the battery to have a stable long-term cycle and good electrochemical performance.
[0032] (4) The present invention provides an application of an electrolyte, which can form a uniform and dense film on the surface of an alkali metal electrode body, and the film-forming conditions have a certain degree of controllability; and the application is to pre-react the alkali metal electrode body with the electrolyte of the present invention before the electrochemical cycle, that is, pre-form a SEI film on the surface of the alkali metal electrode body in advance, to obtain an alkali metal electrode with a SEI film, and then apply the electrode to an alkali metal battery, thereby reducing the consumption of additive molecules during the cycle and being more conducive to the electrostatic shielding effect.
[0033] (5) The present invention provides an alkali metal battery, in which the alkali metal deposition of the alkali metal electrode of the battery is relatively uniform during the cycle, and the growth of alkali metal dendrites is suppressed, so that the safety performance of the battery is improved, and the electrochemical performance of the battery can also be stably exerted at a high level; the assembled alkali metal symmetrical battery has a small polarization, and the coulombic efficiency and capacity retention rate of the whole battery are high, so that a safe and long-lasting alkali metal battery can be obtained, which is conducive to stably improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a graph showing the cycle test results of the button full battery assembled from the experimental group electrolyte and the control group electrolyte in Test Example 1.
[0035] Figure 2 It is the charge and discharge voltage-specific capacity curve of the button full battery assembled by the experimental group electrolyte in Test Example 1 in the first three weeks.
[0036] Figure 3 It is the charge and discharge voltage-specific capacity curve of the button full battery assembled by the experimental group electrolyte in Test Example 2 in the first three weeks. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels or prepared according to literature unless otherwise specified.
[0038] Example 1
[0039] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0040] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) is added to an organic solvent and mixed uniformly to obtain a mixed solvent; the organic solvent is composed of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0041] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0042] Example 2
[0043] A lithium metal battery electrolyte containing tetraacetonitrile copper (I) hexafluorophosphate ([(CH3CN)4Cu]PF6) additive, and a preparation method thereof is as follows:
[0044] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0045] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) hexafluorophosphate ([(CH3CN)4Cu]PF6) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, thereby obtaining a mixed solution, wherein the concentration of [(CH3CN)4Cu]PF6 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]PF6 was 1mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0046] Example 3
[0047] A lithium metal battery electrolyte containing tetraacetonitrile copper (I) trifluoromethanesulfonate ([(CH3CN)4Cu]CF3SO3) additive, and its preparation method is as follows:
[0048] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0049] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, copper (I) tetraacetonitrile trifluoromethanesulfonate ([(CH3CN)4Cu]CF3SO3) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]CF3SO3 is 1 mg mL -1; Let it stand for another 1h, and the concentration of [(CH3CN)4Cu]CF3SO3 is 1mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0050] Example 4
[0051] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0052] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0053] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box were both less than 1 ppm, the temperature in the glove box was controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) was added to the mixed solvent, and magnetic stirring was performed for 1 hour using a magnetic stirrer, and ultrasonic dispersion was performed for 1 hour to achieve uniform mixing, thereby obtaining a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 was 0.5 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 0.5mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0054] Example 5
[0055] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0056] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0057] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box were both less than 1 ppm, the temperature in the glove box was controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) was added to the mixed solvent, and magnetic stirring was performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion was performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 was 1.5 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1.5mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0058] Example 6
[0059] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0060] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0061] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box were both less than 1 ppm, the temperature in the glove box was controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) was added to the mixed solvent, and magnetic stirring was performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion was performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 was 2 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 2mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0062] Example 7
[0063] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0064] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed uniformly to obtain a mixed solvent; the organic solvent is composed of 4-methyl-1,3-dioxolane (4-MeDOL) and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0065] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0066] Example 8
[0067] A lithium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0068] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, LiTFSI is added to an organic solvent and mixed evenly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of LiTFSI is such that the concentration of LiTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0069] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) is added to the mixed solvent, and a magnetic stirrer is used to perform magnetic stirring for 1 hour to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1mg mL -1 An electrolyte, wherein the concentration of LiTFSI is 1 mol / L.
[0070] Example 9
[0071] A lithium metal electrode with a SEI film, the preparation method of which is as follows:
[0072] In a glove box filled with argon gas, with oxygen and water contents in the glove box both less than 1 ppm, the temperature in the glove box is controlled to be 25°C±5°C, and the lithium foil is fully immersed in the electrolyte prepared in Example 1 to allow the lithium metal to pre-react with the electrolyte for 1 hour. After the reaction, a SEI film is formed in situ on the surface of the lithium foil, thereby obtaining a lithium metal electrode having a lithium fluoride-rich SEI film.
[0073] Therefore, the lithium metal electrode is composed of a lithium foil and a SEI film attached to the lithium foil, wherein the SEI film is a lithium fluoride-rich SEI film preformed by adjusting the electrolyte solvation structure by tetraacetonitrile copper (I) tetrafluoroborate.
[0074] Example 10
[0075] A lithium metal electrode with a SEI film, the preparation method of which is as follows:
[0076] In a glove box filled with argon gas, with oxygen and water contents in the glove box both less than 1 ppm, the temperature in the glove box is controlled to be 25°C±5°C, and the lithium foil is fully immersed in the electrolyte prepared in Example 1 to allow the lithium metal to pre-react with the electrolyte for 0.5 h. After the reaction is completed, a SEI film is formed in situ on the surface of the lithium foil, thereby obtaining a lithium metal electrode having a lithium fluoride-rich SEI film.
[0077] Therefore, the lithium metal electrode is composed of a lithium foil and a SEI film attached to the lithium foil, wherein the SEI film is a lithium fluoride-rich SEI film preformed by adjusting the electrolyte solvation structure by tetraacetonitrile copper (I) tetrafluoroborate.
[0078] Embodiment 11
[0079] A lithium metal electrode with a SEI film, the preparation method of which is as follows:
[0080] In a glove box filled with argon gas, with oxygen and water contents in the glove box both less than 1 ppm, the temperature in the glove box is controlled to be 60°C±5°C, and the lithium foil is fully immersed in the electrolyte prepared in Example 1 to allow the lithium metal to pre-react with the electrolyte for 1 hour. After the reaction, a SEI film is formed in situ on the surface of the lithium foil, thereby obtaining a lithium metal electrode having a lithium fluoride-rich SEI film.
[0081] Therefore, the lithium metal electrode is composed of a lithium foil and a SEI film attached to the lithium foil, wherein the SEI film is a lithium fluoride-rich SEI film preformed by adjusting the electrolyte solvation structure by tetraacetonitrile copper (I) tetrafluoroborate.
[0082] Example 12
[0083] A sodium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and its preparation method is as follows:
[0084] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) is added to an organic solvent and mixed uniformly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of NaTFSI is such that the concentration of NaTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0085] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1mg mL -1 An electrolyte, wherein the concentration of NaTFSI in the electrolyte is 1 mol / L.
[0086] Example 13
[0087] A potassium metal battery electrolyte containing tetrafluoroborate tetraacetonitrile copper (I) ([(CH3CN)4Cu]BF4) additive, and a preparation method thereof is as follows:
[0088] (1) In a glove box filled with argon gas, wherein the oxygen and water contents in the glove box are both less than 1 ppm, potassium bistrifluoromethylsulfonyl imide (KTFSI) is added to an organic solvent and mixed uniformly to obtain a mixed solvent; the organic solvent is composed of DOL and DME in a volume ratio of 1:1, and the amount of KTFSI is such that the concentration of KTFSI in the electrolyte prepared in this embodiment is 1 mol / L.
[0089] (2) In the glove box filled with argon gas, the oxygen and water contents in the glove box are both less than 1 ppm, the temperature in the glove box is controlled to be 25°C ± 5°C, tetraacetonitrile copper (I) tetrafluoroborate ([(CH3CN)4Cu]BF4) is added to the mixed solvent, and magnetic stirring is performed for 1 hour using a magnetic stirrer, and then ultrasonic dispersion is performed for 1 hour using an ultrasonic disperser to achieve the purpose of uniform mixing, to obtain a mixed solution, wherein the concentration of [(CH3CN)4Cu]BF4 is 1 mg mL -1 ; After standing for another 1h, the concentration of [(CH3CN)4Cu]BF4 was 1mg mL -1 An electrolyte, wherein the concentration of KTFSI is 1 mol / L.
[0090] Test Example 1
[0091] The electrolyte prepared in Example 1 was used to assemble a button full battery with a lithium metal negative electrode and a LiFePO4 positive electrode (referred to as the experimental group);
[0092] A button full battery (referred to as the control group) was assembled with a commercially available common ether-based electrolyte, a lithium metal negative electrode, and a LiFePO4 positive electrode; the commercially available common ether-based electrolyte consisted of an organic solvent, a LiTFSI electrolyte lithium salt, and a LiNO3 additive; the organic solvent consisted of DOL and DME in a volume ratio of 1:1; in the commercially available common ether-based electrolyte, the concentration of LiTFSI was 1 mol / L, and the mass fraction of LiNO3 was 1%.
[0093] The assembly order of the button cells in the experimental and control groups was as follows: positive electrode shell, positive electrode sheet, 30 μL electrolyte, diaphragm, 30 μL electrolyte, lithium sheet, stainless steel gasket and negative electrode shell; after assembly, the battery was pressed using a punch. -1 ) to carry out charge and discharge test, and the test results are as follows Figure 1 The voltage-specific capacity curve of the experimental group in the first three weeks is shown in Figure 2 shown.
[0094] Depend on Figure 1 It can be seen that although the initial capacity of the full battery in the control group is high and close to the limit specific capacity, the capacity decreases rapidly in the subsequent cycles, and can only produce about 130 mAh g at the 60th week. -1 The specific capacity of the battery was 2.34W, and its coulombic efficiency was not stable, with large fluctuations. The experimental group of full batteries assembled with the electrolyte prepared in Example 1, although the initial capacity was slightly lower than that of the control group full batteries, did not show a significant decrease in capacity during the 60-week cycle, and its coulombic efficiency was relatively stable overall.
[0095] Depend on Figure 2It can be seen that the discharge platform of the battery prepared in the experimental group is a high voltage of 3.35V, the platform is long and stable, and after the irreversible film formation reaction in the first week, the discharge specific capacity is maintained at 160mAh g -1 About, close to its theoretical capacity.
[0096] In addition, scanning electron microscopy was used to characterize the lithium negative electrodes in the lithium metal batteries of the experimental group and the control group after cycling. The test results showed that the lithium metal batteries in the experimental group had a significant effect in inhibiting dendrite growth compared with the lithium metal batteries in the control group.
[0097] Therefore, based on the above test results, it can be seen that the electrolyte prepared in Example 1 can pass Cu + By regulating the electrolyte solvation structure and forming a LiF-rich SEI film, the formation of lithium dendrites and "dead lithium" can be effectively inhibited, the capacity decay of lithium metal batteries can be avoided, and excellent electrochemical performance can be exhibited.
[0098] Test Example 2
[0099] The electrolyte prepared in Example 4 was used to assemble a button full battery with a lithium metal negative electrode and a LiFePO4 positive electrode. The assembly order of the full battery was: positive electrode shell, positive electrode sheet, 30 μL electrolyte, diaphragm, 30 μL electrolyte, lithium sheet, stainless steel gasket and negative electrode shell. After assembly, the battery was pressed using a punch. -1 ) was used for charge and discharge test. The voltage-specific capacity curve of the full battery in the first three cycles (excluding the first cycle) is as follows: Figure 3 shown.
[0100] Depend on Figure 3 It can be seen that the battery also has a long and stable high-voltage discharge platform of ~3.35V, and after experiencing the irreversible film formation reaction in the first week, the discharge capacity is 160mAh g -1 It is close to its theoretical capacity.
[0101] In addition, scanning electron microscopy was used to characterize the lithium negative electrode in the cycled battery, and the test results showed that the battery had a significant effect in inhibiting the growth of lithium dendrites.
[0102] Therefore, based on the above test results, it can be seen that the electrolyte additive introduced into the electrolyte prepared in Example 4 inhibits the growth of lithium dendrites, so that the assembled battery can show relatively good electrochemical performance.
[0103] The alkali metal battery electrolyte or alkali metal electrode provided in other embodiments was tested with reference to the above method. Compared with the unmodified electrolyte or electrode, the electrolyte or alkali metal electrode showed an inhibitory effect on dendrite growth, a higher discharge capacity and better cycle stability, and improved coulombic efficiency. This further illustrates the effect of the additive for regulating the electrolyte solvation structure based on cuprous ions provided by tetraacetonitrile copper (I) salt on improving the performance of the SEI membrane and the significant effect of inhibiting the growth of dendrites in alkali metal batteries.
[0104] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. An application of an alkali metal battery electrolyte, characterized in that: Before the electrochemical cycle, in an inert gas atmosphere with oxygen and water content less than 1 ppm, the alkali metal electrode body is immersed in an electrolyte to allow the alkali metal to pre-react with the electrolyte at a reaction temperature of 20°C to 65°C for a reaction time of 0.5h to 2h. After the reaction is completed, a SEI film is in situ formed on the surface of the alkali metal electrode body, that is, an alkali metal electrode with a SEI film is obtained; The inert gas is helium, neon, argon, krypton, xenon or radon; The electrolyte comprises an organic solvent, an alkali metal salt and an electrolyte additive; in the electrolyte, the concentration of the electrolyte additive is 0.5 mg mL -1 ~2 mg mL -1 ; The electrolyte additive is an ionic liquid composed of tetraacetonitrile copper (I) cations and fluorine-containing Lewis base anions; the fluorine-containing Lewis base anions are one or more of tetrafluoroborate ions, trifluoromethanesulfonate ions, bistrifluoromethylsulfonyl imide ions and bisfluorosulfonyl imide ions.
2. The use of an alkali metal battery electrolyte according to claim 1, characterized in that: The electrolyte additive is one or more of tetraacetonitrile copper (I) tetrafluoroborate and tetraacetonitrile trifluoromethanesulfonate copper (I).
3. The use of an alkali metal battery electrolyte according to claim 1 or 2, characterized in that: The organic solvent is one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, ethylene glycol dimethyl ether, 1,2-dimethoxypropane, diethylene glycol dimethyl ether, N-methylpyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, dimethylformamide, γ-butyrolactone, methyl acetate and ethyl acetate; The alkali metal salt is one or more of alkali metal hexafluorophosphate, alkali metal tetrafluoroborate, alkali metal bistrifluoromethylsulfonyl imide salt and alkali metal perchlorate.
4. The use of an alkali metal battery electrolyte according to claim 3, characterized in that: The organic solvent is composed of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, or 4-methyl-1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, or ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, or ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, or ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1, or ethylene carbonate, dimethyl carbonate and diethyl carbonate in a volume ratio of 1:1:1; the alkali metal salt is one of alkali metal hexafluorophosphate, alkali metal tetrafluoroborate, alkali metal bistrifluoromethylsulfonyl imide and alkali metal perchlorate; in the electrolyte, the concentration of the alkali metal salt is 1 mol / L; In the electrolyte, the concentration of the electrolyte additive is 1 mg mL -1 .
5. The use of an alkali metal battery electrolyte according to claim 1 or 2, characterized in that: The preparation method of the electrolyte comprises the following steps: (1) In an inert gas atmosphere in which the oxygen and water contents are both less than 1 ppm, an alkali metal salt is added to an organic solvent and mixed uniformly to obtain a mixed solvent; (2) Continuing in the above-mentioned inert gas atmosphere, adding the electrolyte additive to the mixed solvent, mixing evenly, and standing for 15 minutes to 60 minutes to obtain the electrolyte; The inert gas is helium, neon, argon, krypton, xenon or radon.
6. The use of an alkali metal battery electrolyte according to claim 5, characterized in that: The electrolyte additive and the mixed solvent are mixed uniformly by means of magnetic stirring and ultrasonic dispersion.
7. The use of an alkali metal battery electrolyte according to claim 6, characterized in that: The mixture was first stirred for 1 hour by magnetic force, and then dispersed by ultrasonic force for 1 hour to make the electrolyte additive and the mixed solvent uniformly mixed.
8. An alkali metal battery, characterized in that: The negative electrode in the battery is an alkali metal electrode with a SEI film as described in claim 1; Alternatively, the electrolyte of the battery is the electrolyte described in claim 1 and the negative electrode in the battery is an alkali metal electrode with a SEI film as described in claim 1.
Citation Information
Patent Citations
Liquid-state electrolyte-based secondary lithium battery without negative electrode
CN107768720A
Non-aqueous redox flow batteries
CN109690855A